A cluster of person-to-person transmission cases caused by SFTS virus in Penglai, China. (March 2015) - Jiang, X.L.; Zhang, S.; Jiang, M.; Bi, Z.Q.; Liang, M.F.; Ding, S.J.; Wang, S.W.; Liu, J.Y.; Zhou, S.Q.; Zhang, X.M.; Li, D.X.; Xu, A.Q.
Abstract: An emerging infectious disease, severe fever with thrombocytopenia syndrome (SFTS), was identified to be associated with a novel SFTS virus (SFTSV). Transmission of the disease among humans has been described, but clinical impact factors and transmission mechanisms still need further study. An outbreak of person-to-person transmission of SFTS in a cluster of nine patients that occurred in an SFTS endemic area, Penglai County, Shandong province, China, was investigated. We found that the onset date of all eight secondary SFTS patients ranged from 7 to 13 days after exposure to the corpse of the index patient, and clinical incubation time was mostly focused on 9–10 days ( n = 6). The two dead patients, including the index patient and one secondary infected patient, presented unusually high levels of viral load (6 × 10 8-9 copies/mL), low levels of platelets count (<55 × 10 9 /L), and significant increase of alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, and creatine kinase values in the second week, and died on day 10 or 11 after disease onset. Genetic sequencing revealed 100% homology among virus strains isolated from the index patient and five secondary patients. Risk factors assessment of the person-to-person transmission revealed that the major exposure factor was blood contact without personal protection equipment. Information from this study provided solid references of SFTS incubation time, clinical and laboratory parameters related to SFTS severity and outcome, and biosafety issues for preventing person-to-person transmission or nosocomial infection of SFTSV.